Optimalisasi Sistem E-Marketplace P Controller (MVC) (Studi Kasus: Inkubator Bisnis Kampus Universitas Global Jakarta) - Listiana, Nora; Anjara, Febria; Ridho, Ali (UNIVERSITAS SERAMBI MEKKAH, 2025)
Jakarta Global University, as a campus that has an economics faculty for the Digital Business study program, offers a platform for students who want to become entrepreneurs as a Business Incubator for various types of businesses, both in the culinary/food sector, convection products, accessories and other service products but currently they are still carrying out the buying and selling process. conventionally. So there are several obstacles in delivering goods or products as well as inputting and checking product data. This research aims to develop an E-Marketplace System that will be created on the JGU E-Commerce Web with a Model View Controller (MVC) architecture to facilitate the operation of the online sales system and increase customer trust in the buying and selling process. The software development model used is the RUP (Rational Unified Process) model with several phases, namely Inception, Elaboration, Construction, and Installation Transition. This research produces an E-marketplace with a view controller model which aims to compete with competitors and to make transactions effective for sellers and buyers and to increase sales.